A Bifunctional Hybrid Electrocatalyst for Oxygen Reduction and Evolution: Cobalt Oxide Nanoparticles Strongly Coupled to B, N‐Decorated Graphene. Issue 25 (19th May 2017) - Tong, Yun; Chen, Pengzuo; Zhou, Tianpei; Xu, Kun; Chu, Wangsheng; Wu, Changzheng; Xie, Yi
Abstract: The electrocatalyzed oxygen reduction and evolution reactions (ORR and OER, respectively) are the core components of many energy conversion systems, including water splitting, fuel cells, and metal–air batteries. Rational design of highly efficient non‐noble materials as bifunctional ORR/OER electrocatalysts is of great importance for large‐scale practical applications. A new strongly coupled hybrid material is presented, which comprises CoO x nanoparticles rich in oxygen vacancies grown on B, N‐decorated graphene (CoO x NPs/BNG) and operates as an efficient bifunctional OER/ORR electrocatalyst. Advanced spectroscopic techniques were used to confirm formation of abundant oxygen vacancies and strong Co−N−C bridging bonds within the CoO x NPs/BNG hybrid. Surprisingly, the CoO x NPs/BNG hybrid electrocatalyst is highly efficient for the OER with a low overpotential and Tafel slope, and is active in the ORR with a positive half‐wave potential and high limiting current density in alkaline medium. Abstract : The Ties That Bind : CoO x nanoparticles were coupled to B, N‐decorated graphene by strong Co−N−C bonds. The hybrid material, which is rich in oxygen vacancies, is a bifunctional electrocatalyst for oxygen evolving and reduction reactions in alkaline conditions.